Early results from the solar-minimum 2019 total solar eclipse. Issue Volume 15:Issue S354(2019) (June 2019) - Pasachoff, Jay M.; Lockwood, Christian A.; Inoue, John L.; Meadors, Erin N.; Voulgaris, Aristeidis; Sliski, David; Sliski, Alan; Reardon, Kevin P.; Seaton, Daniel B.; Caplan, Ronald M.; Downs, Cooper; Linker, Jon A.; et al.
Abstract: We observed the 2 July 2019 total solar eclipse with a variety of imaging and spectroscopic instruments recording from three sites in mainland Chile: on the centerline at La Higuera, from the Cerro Tololo Inter-American Observatory, and from La Serena, as well as from a chartered flight at peak totality in mid-Pacific. Our spectroscopy monitored Fe X, Fe XIV, and Ar X lines, and we imaged Ar X with a Lyot filter adjusted from its original H-alpha bandpass. Our composite imaging has been compared with predictions based on modeling using magnetic-field measurements from the pre-eclipse month. Our time-differenced sites will be used to measure motions in coronal streamers.